Convergent validity of functional communication tools and spoken language comprehension assessment in children with cerebral palsy - Vaillant, Emma; Oostrom, Kim J.; Beckerman, Heleen; Vermeulen, Jeroen R.; Buizer, Annemieke I.; Geytenbeek, Johanna J. M. (International journal of language & communication disorders, 2022)
Background The majority of children with cerebral palsy (CP) experience challenges in functional communication from a young age. A pivotal aspect of functional communication is language comprehension. A variety of classification systems and questionnaires are available to classify and describe functional communication skills in children with CP. A better understanding of the convergent validity of (subsections of) these tools, as well as their relationship with spoken language comprehension, will be valuable in both clinical practice and research. Aims To investigate the convergent validity of (subsections of) functional communication tools and the relationship with spoken language comprehension in children with CP. Methods & Procedures Cross‐sectional data on 138 children were subdivided into three developmental stages based on (Dutch) educational phases: ages 18 months–3;11y (n = 59), 4;0–5;11 years (n = 37) and 6;0–8;11 years (n = 42). The following functional communication tools were used to classify and describe functional communication: Communication Function Classification System (CFCS), subscales of the Caregivers Priorities and Child Health Index of Life with Disabilities—Dutch Version (CPCHILD‐DV) and the Focus on Communication Under Six‐34 (FOCUS‐34) questionnaire. Spoken language comprehension was assessed with the Computer‐Based instrument for Low motor Language Testing (C‐BiLLT). Correlations between the functional communication tools, and with the C‐BiLLT, were calculated using Pearson's and Spearman's correlation coefficients. It was hypothesized a priori that correlations of at least 0.60 suggest good convergent validity. Outcomes & Results At all developmental stages, a significant ordered decreasing tendency of communication outcomes was found across CFCS levels; lower CFCS levels were associated with lower scores on the CPCHILD‐DV and FOCUS‐34, and with a lower level of spoken language comprehension (C‐BiLLT). Correlation coefficients of the functional communication tools exceeded 0.60 at all developmental stages. Correlations between C‐BiLLT raw scores and the functional communication tools varied between 0.351 and 0.591 at developmental stage 18 months–3;11 years, between 0.781 and 0.897 at developmental stage 4;0–5;11 years, and between 0.635 and 0.659 at developmental stage 6;0–8;11 years. Conclusions & Implications The functional communication tools assessed in this study showed convergent validity at all developmental stages. The CFCS, currently most widely used in paediatric rehabilitation, is adequate in the classification of functional communication. However, for more detailed clinical goal setting and evaluation of change in functional communication, the additional use of FOCUS‐34 or CPCHILD‐DV is recommended. What this paper adds What is already known on the subject A range of functional communication tools are available that help describe and classify functional communication in children with CP. These include the CFCS, subsections of CPCHILD‐DV and FOCUS‐34. The CFCS classifies functional communication in daily life with familiar and unfamiliar partners. Specific subsections of the CPCHILD‐DV and FOCUS‐34 include items that pertain to communicative participation. The innovative C‐BiLLT provides a standardized method to assess spoken language comprehension in children with CP and significant motor impairments. What this paper adds to existing knowledge In the present study, convergent validity was confirmed between CFCS and specific subsections of the CPCHILD‐DV and FOCUS‐34. Correlations between these functional communication tools and the C‐BiLLT were moderate to strong. What are the potential or actual clinical implications of this work? For clinical and research purposes (for instance, accurate prescription of augmentative and alternative communication—AAC), healthcare and educational professionals together with parents need to know how functional communication tools converge and how functional communication levels relate to the comprehension of spoken language. The CFCS provides a valid classification of functional communication abilities in children with CP. However, to measure change in functional communication and to evaluate treatment outcomes, use of additional functional communication tools such as the CPCHILD‐DV and FOCUS‐34 is recommended. When discrepancies are found between communicative abilities and spoken language comprehension, it is strongly recommended that valid tools are used in a more detailed examination of the child's spoken language comprehension skills and functional communication.